Supporting Transition to the Workforce for Neurodivergent Learners: Insights from a Canadian Study on the Neuroinclusivity of Post-Secondary Education - Fane, Jennifer; Giacoboni, Liana (GILE Journal of Skills Development, 2025)
This article offers evidence-based recommendations to enhance the neuroinclusivity of post-secondary career education and practices for career educators and student support professionals. The authors share insights from an applied research study that employed a mixed method design that included a national survey of neurodivergent post-secondary students and recent graduates (n=400) and 78 in-depth interviews with neurodivergent students and recent graduates (n=45) and staff and leaders working in accessibility services (n=33). Findings revealed that neurodivergent post-secondary students encountered significant barriers to post-secondary education, which impact graduation rates and successful workforce transitions. Reduction of stigma, improved access to tailored supports, and neuroaffirming approaches to supporting students with potential transition challenges such as employment searching, disclosure, and accommodations were identified as enablers for success. This article presents recommendations from the most comprehensive national data set on neuroinclusivity in Canadian post-secondary education. This article offers actionable recommendations for career educators to use strength-based approaches and reduce employment barriers for neurodivergent individuals.